Separator for electrochemical device and electrochemical device including the same

By forming a coating of a specific composition on the surface of the porous polymer substrate of the separator for an electrochemical device, the problems of environmental pollution and high manufacturing costs caused by the use of organic solvents in the prior art are solved, and efficient battery manufacturing is achieved.

CN119731864APending Publication Date: 2025-03-28LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480003738.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-18
Filing Date
2024-01-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing separators for electrochemical devices need to use organic solvents during the manufacturing process, which leads to environmental pollution and increases manufacturing costs, while insufficient adhesion affects the manufacturing efficiency of the battery.

Method used

By forming a coating containing the first polymer binder particles, the second polymer binder particles and inorganic particles on the surface of the porous polymer substrate, the content of halogen atoms and metal atoms exposed on the coating surface is adjusted to improve dry and wet adhesion and reduce manufacturing costs.

Benefits of technology

It is achieved to improve the adhesion of the separator without using organic solvents, improve battery manufacturing efficiency, and reduce manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731864A_ABST
    Figure CN119731864A_ABST
Patent Text Reader

Abstract

The present invention relates to a separator for an electrochemical device, the separator comprising a porous polymer substrate and a coating layer formed on at least one surface of the porous polymer substrate, in which the amount of halogen atoms exposed on the surface of the coating layer may be 10% by weight or less based on 100% by weight of the total exposed atoms, and the amount of metal atoms exposed on the surface of the coating may be 20% by weight or more based on 100% by weight of the total exposed atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure claims the benefit of the filing date of Korean Patent Application No. 10-2023-0026493 filed in the Korean Intellectual Property Office on February 28, 2023, and the benefit of the filing date of Korean Patent Application No. 10-2024-0007840 filed in the Korean Intellectual Property Office on January 18, 2024, all of which are included in the present disclosure. The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the same, and in particular, to a separator for an electrochemical device and an electrochemical device including the same: the contents of halogen atoms and metal atoms exposed on the surface of a coating are adjusted so that dry adhesion and wet adhesion can be improved, and the heat resistance of the separator can be improved. Background Art

[0002] The separator in the components of the electrochemical device includes a polymer substrate with a porous structure located between the positive electrode and the negative electrode, and is used to isolate the positive electrode and the negative electrode, prevent electrical short circuits between the two electrodes, and allow electrolyte and ions to pass through. The separator itself does not participate in the electrochemical reaction, but physical properties such as wettability to the electrolyte, porosity, thermal shrinkage, etc. affect the performance and safety of the electrochemical device.

[0003] Therefore, in order to enhance the physical properties of the separator, various methods have been tried by adding a coating to the porous polymer substrate and adding various materials to the coating to change the physical properties of the coating. For example, an inorganic material can be added to the coating to improve the mechanical strength of the separator, or an inorganic material or hydrate can be added to the coating to improve the flame retardancy and heat resistance of the polymer substrate.

[0004] The separator may be bonded to the electrode through a lamination process, and a binder resin may be added to the coating slurry of the separator to ensure adhesion between the electrode and the separator.

[0005] Meanwhile, in the case of oil-based slurry coating using an organic solvent such as acetone in the process of forming a coating on the separator, there are restrictions and environmental regulations on manufacturing the separator due to the organic solvent, and there is a problem of increased investment cost due to the need to prepare equipment for processing the organic solvent used in the process of manufacturing the separator. In addition, in order to improve production efficiency by applying lamination and stacking (L (lamination) and S (stacking)) processes in the process of assembling batteries, it is required to ensure adhesion to the separator.

[0006] Therefore, there is a need to study a separator that ensures appropriate adhesion for performing lamination and stacking processes and does not use an organic solvent in a separator manufacturing process. Summary of the invention

[0007] Technical issues

[0008] The technical problem to be achieved by the present disclosure is to provide a separator for an electrochemical device and an electrochemical device including the same, wherein the separator for an electrochemical device adjusts the type and amount of atoms located on the surface of a coating layer to maintain adhesion during the manufacture of a secondary battery in which an electrode and a separator are layered, and since no organic solvent is included in a slurry for preparing the coating layer, no separate solvent treatment equipment is required.

[0009] However, problems to be solved by the present disclosure are not limited to the above-mentioned problems, and other problems not mentioned will be clearly understood by those skilled in the art through the following description.

[0010] Technical Solution

[0011] One embodiment of the present disclosure provides a separator for an electrochemical device, which includes: a porous polymer substrate; and a coating disposed on at least one surface of the porous polymer substrate and comprising first polymer binder particles, second polymer binder particles and inorganic particles, wherein based on 100 weight % of the total atoms exposed from the surface of the coating, the content of halogen atoms exposed from the surface of the coating (the opposite surface of one surface of the porous polymer substrate) is 10 weight % or less; and based on 100 weight % of the total atoms exposed from the surface of the coating, the content of metal atoms exposed from the surface of the coating is 20 weight % or greater.

[0012] According to one embodiment of the present disclosure, a ratio of a content of halogen atoms exposed from the surface of the coating measured in weight % based on 100 weight % of total atoms exposed from the surface of the coating to a content of halogen atoms in the coating measured in weight % based on 100 weight % of total atoms in the coating is in a range of 0.5 to 2.5.

[0013] According to one embodiment of the present disclosure, a ratio of a content of metal atoms exposed from the surface of the coating measured in weight % based on 100 weight % of total atoms exposed from the surface of the coating to a content of halogen atoms exposed from the surface of the coating measured in weight % based on 100 weight % of total atoms exposed from the surface of the coating is in a range of 2.5 to 10.

[0014] According to one embodiment of the present disclosure, the content of halogen atoms exposed from the surface of the coating layer may be 1 wt % or more and 10 wt % or less based on 100 wt % of total atoms exposed from the surface of the coating layer.

[0015] According to one embodiment of the present disclosure, the content of metal atoms exposed from the surface of the coating layer may be 20 wt % or more and 50 wt % or less based on 100 wt % of total atoms exposed from the surface of the coating layer.

[0016] According to one embodiment of the present disclosure, the surface of the coating is uniformly distributed with pores.

[0017] According to one embodiment of the present disclosure, the surface of the coating has a predominantly uniformly distributed particle-based morphology.

[0018] According to one embodiment of the present disclosure, the first polymer binder particles may be acrylic binder particles, and / or the second polymer binder particles may be polyvinylidene-based binders.

[0019] According to one embodiment of the present disclosure, the polyvinylidene-based binder may be a copolymer of polyvinylidene fluoride and hexafluoropropylene.

[0020] According to one embodiment of the present disclosure, the halogen atom may be a fluorine atom.

[0021] According to one embodiment of the present disclosure, the metal atom may be one selected from the following: Al, Ba, Ti, Pb, Zr, La, Mg, Nb, Sr, Si, Y, Zn, Sn, Sb, Pt and combinations thereof, and / or the metal atom is derived from inorganic particles of the coating, wherein the inorganic particles are selected from BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT,0 <x<1,0<y<1)、Pb(Mg 1 / 3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), tin-zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5) and combinations thereof, preferably Al2O3.

[0022] According to one embodiment of the present disclosure, the dry adhesion of the coating layer may be 35 gf / 20 mm or more.

[0023] According to one embodiment of the present disclosure, the wet adhesion of the coating layer may be 10 gf / 20 mm or more.

[0024] One embodiment of the present disclosure provides an electrochemical device including: a positive electrode; a negative electrode; and a separator interposed between the positive electrode and the negative electrode.

[0025] According to one embodiment of the present disclosure, the positive electrode includes a positive electrode active material layer, and the coating of the separator is in direct contact with the positive electrode active material layer; and / or wherein the negative electrode includes a negative electrode active material layer, and the coating of the separator is in direct contact with the negative electrode active material layer.

[0026] Beneficial Effects

[0027] The separator for an electrochemical device according to one embodiment of the present disclosure may be appropriately provided with a halogen element and a metal element on the surface of a coating layer, and improve dry adhesive force and wet adhesive force, thereby improving battery manufacturing efficiency.

[0028] An electrochemical device according to an embodiment of the present disclosure may reduce manufacturing costs and may facilitate manufacturing of the electrochemical device due to improvement in adhesion of a separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 (a) and Figure 1 (b) is a schematic diagram of a separator for an electrochemical device according to one embodiment of the present disclosure. Specifically, Figure 1 (a) is a schematic diagram of a separator for an electrochemical device having a coating provided on one surface, and Figure 1 (b) is a schematic diagram of a separator for an electrochemical device having coating layers on both surfaces.

[0030] Figure 2 is a schematic diagram of an electrochemical device according to one embodiment of the present disclosure.

[0031] Figure 3 are a photograph of the surface of Example 1 according to one embodiment of the present disclosure taken by energy dispersive X-ray spectroscopy (EDS) and a table showing the contents of elements provided on the surface.

[0032] Figure 4 : is a photograph of the surface of Comparative Example 1 taken by EDS and a table showing the contents of elements provided on the surface.

[0033] Figure 5 : is a photograph of the surface of Comparative Example 2 taken by EDS and a table showing the contents of elements provided on the surface.

[0034] Figure 6 : is a photograph of the surface of Comparative Example 3 taken by EDS and a table showing the contents of elements provided on the surface.

[0035] Figure 7 : is a photograph of the surface of Comparative Example 4 taken by EDS and a table showing the contents of elements provided on the surface.

[0036] Figure 8 : is a photograph of the surface of Comparative Example 5 taken by EDS and a table showing the contents of elements provided on the surface.

[0037] Fig. 9 : are a photograph of the surface of Example 2 according to one embodiment of the present disclosure taken by EDS and a table showing the contents of elements provided on the surface. DETAILED DESCRIPTION

[0038] Hereinafter, multiple embodiments of the present disclosure will be described in detail so that those skilled in the art to which the present disclosure belongs can easily perform the present disclosure. However, these are merely examples given for illustrative purposes, and the scope of the present disclosure is not intended to be limited to the following.

[0039] Unless otherwise limited, the detailed description of the defined or specified elements can be applied to all inventions and is not limited to the description of a specific invention. That is, the present disclosure also relates to a combination of embodiments, even if they are disclosed separately. In addition, unless otherwise explicitly stated, throughout the detailed description and the appended claims, the singular includes the plural.

[0040] In this specification, when a part is said to "comprise" a certain component, unless otherwise specifically stated, this means that it may also include other components without excluding other components. However, unless otherwise clearly stated, "comprising" or "including" etc. include "essentially comprising" and "consisting of . . . . ".

[0041] As used herein, the term "essentially comprising" has the meaning of "comprising at least 70%", preferably the meaning of "comprising at least 80%", most preferably the meaning of "comprising at least 90%. If referring to the amount of a component in a mixture of materials, % is the % by weight relative to the total weight of the respective mixture. For example, a material essentially comprising polyethylene comprises polyethylene in an amount of at least 70 wt.-% relative to the total weight of the material.

[0042] In the present specification, "A and / or B" means "A and B, or A or B".

[0043] In this specification, when a component is referred to as being disposed "on" another component, unless otherwise specifically stated, this does not exclude that another component is disposed therebetween, but means that another component may also be disposed therebetween. However, unless otherwise explicitly stated, "on..." encompasses the meaning of "directly on...", that is, the case where no other component may also be disposed therebetween.

[0044] In this specification, the property of "having pores" or "porous" means that the object contains a plurality of pores, and thus gas phase fluid and / or liquid phase fluid can pass from one side of the object to the other side thereof through a structure in which the pores are interconnected.

[0045] In this specification, the separator has a porous property including a plurality of pores, and functions as a porous ion-conducting barrier to allow ions to pass therethrough while blocking electrical contact between a negative electrode and a positive electrode in an electrochemical device.

[0046] Hereinafter, the present disclosure will be described in more detail.

[0047] One embodiment of the present disclosure provides a separator 100 for an electrochemical device, comprising: a porous polymer substrate 110; and a coating 130 disposed on at least one surface of the porous polymer substrate 110 and comprising first polymer binder particles 131, second polymer binder particles 133, and inorganic particles 135, wherein the content of halogen atoms exposed from a surface of the coating 130 (the opposite surface to one surface of the porous polymer substrate 110) is 10 wt% or less of the total atoms exposed from the surface of the coating 130 based on 100 wt%, and the content of metal atoms exposed from the surface of the coating 130 is 20 wt% or greater based on 100 wt% of the total atoms exposed from the surface of the coating 130.

[0048] The separator 100 for an electrochemical device according to one embodiment of the present disclosure may be appropriately provided with a halogen element and a metal element on the surface of the coating layer 130 , and improve dry adhesive force and wet adhesive force, thereby improving battery manufacturing efficiency.

[0049] Figure 1 (a) and Figure 1 (b) is a schematic diagram of a separator 100 for an electrochemical device according to one embodiment of the present disclosure. Specifically, Figure 1 (a) is a schematic diagram of a separator for an electrochemical device having a coating provided on one surface, and Figure 1 (b) is a schematic diagram of a separator for an electrochemical device having coatings on both surfaces. Figure 1 (a) and Figure 1 (b) of the present disclosure will now be described in detail the separator 100 for an electrochemical device according to one embodiment of the present disclosure.

[0050] According to one embodiment of the present disclosure, the electrochemical device separator 100 includes the porous polymer substrate 110. As described above, since the electrochemical device separator 100 includes the porous polymer substrate 110, it allows lithium ions to pass through while blocking electrical contact and enables a shutdown function at an appropriate temperature.

[0051] According to one embodiment of the present disclosure, the porous polymer substrate 110 can be manufactured by using a polyolefin-based resin as a base resin. Examples of polyolefin-based resins may include polyethylene, polypropylene, polypentene, etc., and may include one or more thereof. A porous separator (i.e., a separator having a large number of pores) prepared using such a polyolefin-based resin as a base resin can impart a shutdown function at an appropriate temperature.

[0052] According to one embodiment of the present disclosure, the weight average molecular weight of the polyolefin-based resin may be 500,000 or more and 1,500,000 or less. The compression resistance of the separator may be improved by adjusting the weight average molecular weight of the polyolefin-based resin within the above range. In addition, when different kinds of polyolefin-based resins are mixed and used or when a separator is formed with a multilayer structure made of different kinds of polyolefin-based resins, the weight average molecular weight of the polyolefin-based resin may be calculated by adding the weight average molecular weights according to the content ratios of the respective polyolefin-based resins.

[0053] In the present specification, the weight average molecular weight (Mw) may be measured by gel permeation chromatography (GPC, PLGPC220, Agilent Technologies), and the measurement conditions may be set as follows.

[0054] -Column: PL Olexis (Polymer Laboratories)

[0055] -Solvent: TCB (trichlorobenzene)

[0056] -Flow rate: 1.0ml / min

[0057] -Sample concentration: 1.0mg / ml

[0058] -Injection volume: 200μl

[0059] - Column temperature: 160℃

[0060] -Detector: Agilent high temperature RI detector

[0061] -Standard: Polystyrene (calibrated by cubic function)

[0062] According to one embodiment of the present disclosure, the porous polymer substrate 110 can be manufactured by the following method (wet method): kneading a polyolefin-based resin with a plasticizer (diluent) at a high temperature to make a single phase, phase-separating the polymer material and the plasticizer during cooling, and then extracting the plasticizer to form pores, and then stretching and heat-setting the resulting material. In addition, the porous polymer substrate using a polyolefin-based resin may include a core made of a mixture of polyethylene and polypropylene and a polyethylene surface layer laminated on both surfaces of the core.

[0063] According to one embodiment of the present disclosure, those skilled in the art can easily adjust the average size and maximum size of the pores of the separator 100 by adjusting the mixing ratio of the plasticizer, the stretching ratio, the heat setting treatment temperature, etc. to meet the scope of the present disclosure.

[0064] According to one embodiment of the present disclosure, the thickness of the porous polymer substrate may be 1 μm or more and 50 μm or less. Specifically, the thickness of the porous polymer substrate may be 2 μm or more and 45 μm or less, 3 μm or more and 40 μm or less, 4 μm or more and 35 μm or less, 5 μm or more and 30 μm or less, 6 μm or more and 25 μm or less, 7 μm or more and 20 μm or less, or 8 μm or more and 15 μm or less. By adjusting the thickness of the porous polymer substrate within the above range, the energy density of the battery can be improved.

[0065] According to one embodiment of the present disclosure, the porosity of the porous polymer substrate may be 10% by volume or more and 90% by volume or less. Specifically, the porosity of the porous polymer substrate may be 10% by volume or more and 90% by volume or less, 20% by volume or more and 80% by volume or less, 30% by volume or more and 70% by volume or less, or 40% by volume or more and 60% by volume or less. The separator permeability of lithium ions can be controlled by adjusting the porosity of the porous polymer substrate within the above range.

[0066] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device includes a coating 130 disposed on at least one surface of a porous polymer substrate 110. Specifically, the separator 100 for an electrochemical device includes a coating 130 disposed on one or both surfaces of the porous polymer substrate 110. As described above, since the separator 100 for an electrochemical device includes a coating 130 disposed on at least one surface of the porous polymer substrate 110, the heat resistance of the separator can be improved, its mechanical properties can be improved, and the occurrence of an electrical short circuit of the electrode due to the shrinkage of the separator at high temperatures can be prevented. According to one embodiment of the present disclosure, the coating 130 includes first polymer binder particles 131, second polymer binder particles 133, and inorganic particles 135. As described above, since the coating 130 includes first polymer binder particles 131, second polymer binder particles 133, and inorganic particles 135, the heat resistance of the separator can be improved, its mechanical properties can be improved, the occurrence of an electrical short circuit of the electrode due to the shrinkage of the separator at high temperatures can be prevented, and pores can be formed in the coating.

[0067] According to one embodiment of the present disclosure, the coating 130 may include a plurality of pores. Specifically, the coating may be a porous coating. More specifically, the coating may be a porous coating including a plurality of pores therein. As described above, since the coating includes a plurality of pores, current can be allowed to flow by allowing lithium ions to pass therethrough while physically blocking the negative electrode and the positive electrode.

[0068] According to one embodiment of the present disclosure, inorganic particles 135 may be bound and integrated into the coating by first polymer binder particles 131 and second polymer binder particles 133 to form coating 130. The pores inside coating 130 may be due to interstitial volumes, which are empty spaces between inorganic particles.

[0069] According to an embodiment of the present disclosure, the coating layer 130 may be formed to a thickness of 1 μm to 20 μm on either side of the porous polymer substrate 110 , but is not particularly limited thereto. Those skilled in the art may adjust the thickness within an appropriate range according to heat resistance or electrical resistance.

[0070] In one embodiment of the present disclosure, the thickness of the porous polymer substrate and / or coating can be measured by applying a contact-type thickness gauge. As a contact-type thickness gauge, for example, Mitutoyo's VL-50S-B can be used.

[0071] According to one embodiment of the present disclosure, the content of halogen atoms exposed from the surface of the coating 130 is 10 wt% or less based on 100 wt% of the total atoms exposed from the surface of the coating, the surface of the coating 130 being the opposite surface of one surface on which the porous polymer substrate 110 is disposed. Specifically, the content of halogen atoms exposed from the surface of the coating 130 may be greater than 0 wt% and 10 wt% or less, 1 wt% or more and 9 wt% or less, 2 wt% or more and 8 wt% or less, 3 wt% or more and 7 wt% or less, or 4 wt% or more and 6 wt% or less based on 100 wt% of the total atoms exposed from the surface of the coating, the surface of the coating 130 being the opposite surface of one surface on which the porous polymer substrate 110 is disposed. By adjusting the content of halogen atoms exposed from the surface of the coating 130 within the above range, the wet adhesion of the separator may be improved, the rigidity of the pouch-type battery cell may be improved, and the bending thereof may be prevented.

[0072] According to one embodiment of the present disclosure, the content of metal atoms exposed from the surface of the coating layer 130 is 20 wt % or more based on 100 wt % of total atoms exposed from the surface of the coating layer 130 . Specifically, the content of metal atoms exposed from the surface of the coating 130, based on 100 wt % of the total atoms exposed from the surface of the coating 130, may be 21 wt % or more and 49 wt % or less, 22 wt % or more and 48 wt % or less, 23 wt % or more and 47 wt % or less, 24 wt % or more and 46 wt % or less, 25 wt % or more and 45 wt % or less, 26 wt % or more and 44 wt % or less, 27 wt % or more and 43 wt % or less, 28 wt % or more and 42 wt % or less, 29 wt % or more and 41 wt % or less, 30 wt % or more and 40 wt % or less, 31 wt % or more and 39 wt % or less, 32 wt % or more and 38 wt % or less, 33 wt % or more and 37 wt % or less, or 34 wt % or more and 36 wt % or less. By adjusting the content of metal atoms exposed from the surface of the coating layer 130 within the above range, heat resistance of the separator may be improved, wet adhesion of the separator may be improved, rigidity of the pouch type battery cell may be improved, and bending thereof may be prevented.

[0073] According to one embodiment of the present disclosure, the ratio of the content of the halogen atoms exposed from the surface of the coating by weight % based on 100% by weight of the total atoms exposed from the surface of the coating to the content of the halogen atoms in the coating by weight % based on 100% by weight of the total atoms in the coating is in the range of 0.5 to 2.5, 0.55 to 2.0, 0.60 to 1.5, 0.6 to 1.0. In other words, the ratio of the halogen exposed from the surface to the halogen atoms contained in the coating is in the range of 0.5 to 2.5, wherein the halogen atoms exposed from the surface of the coating are measured by weight % based on 100% by weight of the total atoms exposed from the surface of the coating. The above range can be 0.5 to 2.5, 0.55 to 2.0, 0.60 to 1.5, 0.6 to 1.0. The total atoms (including halogens, metals, etc.) exposed from the surface of the coating can be measured by EDS as further defined above. The content of halogen atoms in the coating in wt % based on 100 wt % of the total atoms in the coating can be determined according to the manufacture of the coating. Alternatively, as known to those skilled in the art, the content and composition of the coating can be determined by elemental analysis (e.g., ICP-OES). As a wt % relative to 100 wt % of the total atoms in the coating, it can be determined according to the manufacture of the coating. Alternatively, as known to those skilled in the art, the content and composition of the coating can be determined by elemental analysis (e.g., ICP-OES).

[0074] According to one embodiment of the present disclosure, the ratio of the content of metal atoms exposed from the surface of the coating by weight % based on 100 wt % of the total atoms exposed from the surface of the coating to the content of halogen atoms exposed from the surface of the coating by weight % based on 100 wt % of the total atoms exposed from the surface of the coating is in the range of 2.5 to 10, 3.5 to 9, 4.5 to 8.5, 5.5 to 8.0, 6.5 to 7.5. The total atoms (including halogens, metals, etc.) exposed from the surface of the coating can be measured by EDS as further defined above.

[0075] According to one embodiment of the present disclosure, the content of halogen atoms exposed from the surface of the coating 130 and the content of metal atoms exposed from the surface of the coating 130 may refer to those analyzed by energy dispersive X-ray spectroscopy (EDS) (Hitachi, S-4800). More specifically, they may refer to: after photographing the surface of the coating, for the photographed image, under the condition of an accelerating voltage of 15.0 kV, the weight of the elements shown by energy dispersive X-ray spectroscopy (EDS) analysis (magnification: X 10,000; resolution: 1280×960; secondary electron mode; accelerating voltage: 15 kV; working distance: 15 mm; detector: silicon drift detector).

[0076] According to one embodiment of the present disclosure, the first polymer binder particles 131 may be an acrylic binder. As described above, the acrylic binder is selected as the material of the first polymer binder particles 131, so that the porosity of the separator can be maintained, and the adhesion between the electrode and the separator is improved during the lamination process of the battery, so that the battery can be easily manufactured and the stacking process can be stably implemented.

[0077] According to one embodiment of the present disclosure, the acrylic binder is a polymer including carboxylic acid ester as a repeating unit, and may be preferably (meth)acrylate or acrylic-styrene copolymer.

[0078] According to one embodiment of the present disclosure, specific examples of (meth)acrylates may include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, and the like, and may be one or more selected from them. The (meth)acrylate is preferably one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, and particularly preferably methyl (meth)acrylate.

[0079] According to one embodiment of the present disclosure, the acrylic-styrene copolymer may include an acrylic binder, and the acrylic binder may be a polyacrylate binder. For example, the acrylic binder may include one or more selected from the following: styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and an acrylate-based polymer, and specifically, may be a copolymer containing acrylate.

[0080] According to one embodiment of the present disclosure, the glass transition temperature (Tg) of the first polymer binder particles 131 may be 20°C or more and 60°C or less. Specifically, the glass transition temperature (Tg) of the first polymer binder particles may be 22°C or more and 58°C or less, 24°C or more and 56°C or less, 26°C or more and 54°C or less, 28°C or more and 52°C or less, 30°C or more and 50°C or less, 32°C or more and 48°C or less, 34°C or more and 46°C or less, 36°C or more and 44°C or less, or 38°C or more and 42°C or less. The glass transition temperature (Tg) of the first polymer binder particles is adjusted within the above range so that the viscosity of the slurry used to prepare the coating layer can be adjusted to improve the convenience of battery manufacturing.

[0081] According to one embodiment of the present disclosure, the average diameter (D 50 ) is not particularly limited, but is preferably within a range of 0.1 μm or more and 1 μm or less in order to form a coating layer 130 having a uniform thickness and appropriate porosity. Specifically, the average diameter (D 50 ) may be 0.2 μm or more and 0.9 μm or less, 0.3 μm or more and 0.8 μm or less, 0.4 μm or more and 0.7 μm or less, or 0.5 μm or more and 0.6 μm or less. The average diameter (D 50 ) is adjusted within the above range, so that the dispersibility in the slurry prepared for coating preparation can be improved and the thickness of the formed coating can be reduced.

[0082] According to one embodiment of the present disclosure, the second polymer binder particles 133 may be a polyvinylidene-based binder. Specifically, according to one embodiment of the present disclosure, the polyvinylidene-based binder may be a copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP). As described above, the second polymer binder particles 133 are selected as a polyvinylidene-based binder so that the porosity of the separator can be maintained, and even if the coating is wetted by the electrolyte after the battery is activated, the adhesion can be maintained. In addition, the rigidity of the battery can be improved, and the bending of the separator can be prevented.

[0083] According to one embodiment of the present disclosure, the second polymer binder particles 133 may be a polyvinylidene-based binder in which hexafluoropropylene (HFP) is contained in an amount of 1 wt % or more and 50 wt % or less. Specifically, the second polymer binder particles 133 may be a polyvinylidene-based binder in which hexafluoropropylene (HFP) is contained in an amount of 1 wt % or more and 50 wt % or less, 2 wt % or more and 45 wt % or less, 3 wt % or more and 40 wt % or less, 4 wt % or more and 35 wt % or less, 5 wt % or more and 30 wt % or less, 7 wt % or more and 25 wt % or less, or 10 wt % or more and 20 wt % or less. As described above, the second polymer binder particles 133 are selected as a polyvinylidene-based binder in which hexafluoropropylene is included in an amount of 1 wt % or more and 50 wt % or less, so that the porosity of the separator can be maintained, and even if the coating is wetted by the electrolyte after the battery is activated, the adhesive force can be maintained. In this specification, the degree of substitution of the polyvinylidene-based binder may mean a weight ratio of hexafluoropropylene included.

[0084] According to one embodiment of the present disclosure, the average diameter (D 50 ) is not particularly limited, but is preferably within a range of 0.1 μm or more and 1 μm or less in order to form a coating layer 130 having a uniform thickness and appropriate porosity. Specifically, the average diameter (D 50 ) may be 0.2 μm or more and 0.9 μm or less, 0.3 μm or more and 0.8 μm or less, 0.4 μm or more and 0.7 μm or less, or 0.5 μm or more and 0.6 μm or less. The average diameter (D 50 ) is adjusted within the above range, so that the dispersibility in the slurry prepared for preparing the coating can be improved and the thickness of the formed coating can be reduced.

[0085] According to one embodiment of the present disclosure, the total content of the first polymer binder particles 131 and the second polymer binder particles 133 may be 25 parts by weight or less with respect to 100 parts by weight of the coating layer 130 . Specifically, the total content of the first polymer binder particles 131 and the second polymer binder particles 133 may be greater than 0 parts by weight and 25 parts by weight or less, 1 part by weight or more and 24 parts by weight or less, 2 parts by weight or more and 23 parts by weight or less, 3 parts by weight or more and 22 parts by weight or less, 4 parts by weight or more and 21 parts by weight or less, 5 parts by weight or more and 20 parts by weight or less, 6 parts by weight or more and 19 parts by weight or less, 7 parts by weight or more and 18 parts by weight or less, 8 parts by weight or more and 17 parts by weight or less, 9 parts by weight or more and 16 parts by weight or less, 10 parts by weight or more and 15 parts by weight or less, 11 parts by weight or more and 14 parts by weight or less, or 12 parts by weight or more and 13 parts by weight or less, based on 100 parts by weight of the coating layer 130. The total content of the first polymer binder particles 131 and the second polymer binder particles 133 is adjusted within the above range so that the ease of assembly in the process of assembling the electrode can be improved.

[0086] According to one embodiment of the present disclosure, the weight ratio of the first polymer binder particles 131 to the second polymer binder particles 133 in the coating layer 130 may be 9:1 to 1:9. Specifically, the weight ratio of the first polymer binder particles 131 to the second polymer binder particles 133 in the coating layer 130 may be 8:1 to 1:8, 7:1 to 1:7, 6:1 to 1:6, 5:1 to 1:5, 4:1 to 1:4, 3:1 to 1:3, or 2:1 to 1:2. By adjusting the weight ratio of the first polymer binder particles to the second polymer binder particles within the above range, the wet adhesion and dry adhesion of the separator for an electrochemical device can be improved at the same time, and the content of fluorine atoms exposed on the surface of the coating layer can be adjusted.

[0087] According to one embodiment of the present disclosure, the inorganic particles 135 may be included in an amount of greater than 75 parts by weight based on 100 parts by weight of the coating layer 130. Specifically, the inorganic particles 135 may be included in an amount of greater than 75 parts by weight and less than 100 parts by weight, 76 parts by weight or more and 99 parts by weight or less, 77 parts by weight or more and 98 parts by weight or less, 78 parts by weight or more and 97 parts by weight or less, 79 parts by weight or more and 96 parts by weight or less, 80 parts by weight or more and 95 parts by weight or less, 81 parts by weight or more and 94 parts by weight or less, 82 parts by weight or more and 93 parts by weight or less, 83 parts by weight or more and 92 parts by weight or less, 84 parts by weight or more and 91 parts by weight or less, 85 parts by weight or more and 90 parts by weight or less, 86 parts by weight or more and 89 parts by weight or less, or 87 parts by weight or more and 88 parts by weight or less. Adjusting the content of the inorganic particles 135 within the above range makes it possible to improve the heat resistance of the separator.

[0088] According to one embodiment of the present disclosure, the inorganic particles 135 that can be used in the coating layer 130 are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in one embodiment of the present disclosure are not particularly limited as long as they are within the operating voltage range of the applied electrochemical device (e.g., based on Li / Li + Those that do not undergo oxidation and / or reduction reactions (0V to 5V) are sufficient.

[0089] According to one embodiment of the present disclosure, non-limiting examples of the inorganic particles 135 may include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT,0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), tin-zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5), etc., and may include one of them, or two or more of them.

[0090] According to one embodiment of the present disclosure, the average diameter (D50 ) is not particularly limited, but is preferably within a range of 0.3 μm or more and 1 μm or less in order to form a coating layer 130 having a uniform thickness and appropriate porosity. Specifically, the average diameter (D 50 ) may be 0.2 μm or more and 0.9 μm or less, 0.3 μm or more and 0.8 μm or less, 0.4 μm or more and 0.7 μm or less, or 0.5 μm or more and 0.6 μm or less. Specifically, when the average diameter is less than 0.3 μm, the dispersibility of the inorganic particles in the slurry prepared for preparing the coating may be reduced, and when the average diameter exceeds 1 μm, the thickness of the coating to be formed may increase.

[0091] In this manual, "D 50 "Particle size" means the particle size at the 50% point of the cumulative distribution of the number of particles according to the particle size. The particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern according to the particle size when the particle passes through the laser beam, thereby calculating the particle size distribution. The particle size distribution can be measured by calculating the particle size at the point where the particle size distribution in the measuring device becomes 50% of the cumulative distribution of the number of particles according to the particle size. 50 Particle size. D can be measured according to ISO13320-1 (particle size analysis - laser diffraction method) 50 Particle size.

[0092] According to one embodiment of the present disclosure, the porosity of the coating 130 may be 30% by volume or more. Specifically, the porosity of the coating 130 may be 30% by volume or more and 70% by volume or less, 32% by volume or more and 68% by volume or less, 34% by volume or more and 66% by volume or less, 36% by volume or more and 64% by volume or less, 38% by volume or more and 62% by volume or less, 40% by volume or more and 60% by volume or less, 42% by volume or more and 58% by volume or less, 44% by volume or more and 56% by volume or less, 46% by volume or more and 54% by volume or less, or 48% by volume or more and 52% by volume or less. The porosity of the coating 130 is adjusted within the above range so that the movement of ions in the separator can be maintained and the resistance of the separator can be prevented from increasing. Specifically, if the porosity is 70% by volume or less, it is possible to ensure dynamic characteristics that can withstand the pressing process of bonding it to the electrode, and since the surface open porosity does not become too high, it is also suitable for ensuring adhesion. At the same time, when the porosity is 30% by volume or more, it is advantageous in terms of ion permeability.

[0093] In the present specification, "porosity" means the ratio of the volume occupied by pores with respect to the total volume, uses volume % as its unit, and may be used interchangeably with terms such as void ratio and porosity.

[0094] In the present specification, the porosity may correspond to a value obtained by subtracting a volume converted by the weight and density of each component of the porous polymer substrate 110 and / or the coating 130 from a volume calculated by the thickness, width, and length of the porous polymer substrate 110 and / or the coating 130 .

[0095] In one embodiment of the present disclosure, the porosity and pore size of the porous polymer substrate 110 and / or the coating 130 can be measured by using a scanning electron microscope (SEM) image, a mercury porosimeter or a capillary flow porosimeter (poretech's iCFP-1100), or by a BET 6-point method using a porosimetry analyzer (Bell Japan Inc, Belsorp-II mini) by a nitrogen adsorption flow method. At this time, it may be advantageous to use a capillary flow porosimeter, which can be measured according to ASTM-F316.

[0096] According to one embodiment of the present disclosure, the surface of the coating can be evenly distributed with holes. Therefore, the coating can be evenly distributed on the surface of the coating. When an electron image of 60 μm × 60 μm is taken, the uniform distribution can produce consistent pore size and shape on the entire surface, which can be measured by SEM. The pore size on the surface of the coating can be 30 μm or less, 25 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, 5 μm or less, 3 μm or less, or 2 μm or less, but the pore size can be 0.001 μm or more, 0.01 μm or more, such as in the range of 0.001 μm to 30 μm. When an electron image of 60 μm × 60 μm is taken, the pore size on the surface of the coating can be measured by SEM. Alternatively, as known to those skilled in the art, the pore size can be measured as defined above. When taking a 60 μm x 60 μm electron image, a uniform distribution may show a regular pattern or spacing of holes across the surface, which can be measured by SEM.

[0097] According to one embodiment of the present disclosure, the surface of the coating may have a mainly uniformly distributed particle-based morphology. "Mainly uniformly distributed particle-based morphology" on the surface of the coating may refer to a unique pattern and arrangement of particles that exhibit a high degree of uniformity and regularity. The coating may show a uniform distribution of particles per unit area. A unit area may be an electron image of 60 μm×60 μm measured by SEM. In the mainly uniformly distributed particle-based morphology, the particles may be spaced uniformly so that there may be no areas with significantly higher or lower particle concentrations. The particles may maintain a consistent shape over the entire surface. The shape may be spherical, angular, or another shape, and its morphology may remain unchanged so that it may contribute to overall uniformity, thereby having a mainly uniformly distributed particle-based morphology.

[0098] According to one embodiment of the present disclosure, the polyvinylidene-based binder may be an aqueous binder. Specifically, the polyvinylidene-based binder is selected as an aqueous binder, and thus the manufacturing cost of the battery can be reduced by minimizing pollutants discharged during the separator preparation process.

[0099] According to an embodiment of the present disclosure, an adhesive polymer binder may be provided on the coating 130. Specifically, the adhesive polymer binder may be provided on the surface of the coating opposite to the surface adjacent to the porous polymer substrate. More specifically, the opposite surface of the coating is covered with the adhesive polymer binder. As described above, by providing the adhesive polymer binder on the coating 130, the dry adhesion and wet adhesion to the electrode are improved, respectively.

[0100] According to an embodiment of the present disclosure, the adhesive polymer binder may be a particle type, a solution type, and a combination thereof. In this specification, "particle type" may define an adhesive polymer binder that maintains a particle phase by not being dissolved by an electrolyte embedded in a battery cell. In this specification, "solution type" may define an adhesive polymer binder that does not maintain a particle phase by being dissolved by an electrolyte embedded in a battery cell. By selecting the type of adhesive polymer binder described above, the dry adhesion and wet adhesion to the electrode are improved, respectively.

[0101] According to an embodiment of the present disclosure, an adhesive polymer binder is disposed on a portion of the coating layer 130. As described above, by disposing the adhesive polymer binder on a portion of the coating layer 130, dry adhesion and wet adhesion to the electrode are improved, respectively.

[0102] According to an embodiment of the present disclosure, based on the total area of ​​the coating, the adhesive polymer binder is set to an area greater than 0% and less than 100%. Specifically, based on the total area of ​​the coating, the adhesive polymer binder is set to an area of ​​1% or more and 99% or less, 5% or more and 95% or less, 10% or more and 90% or less, 15% or more and 85% or less, 20% or more and 80% or less, 25% or more and 75% or less, 30% or more and 70% or less, 35% or more and 65% or less, 40% or more and 60% or less, or 45% or more and 55% or less. The area set on the coating by the adhesive polymer binder is adjusted within the above range, and the dry adhesion and wet adhesion to the electrode are improved respectively.

[0103] According to an embodiment of the present disclosure, the adhesive polymer binder may be the same as the first polymer binder and the second polymer binder, or may be different from the first polymer binder and the second polymer binder. Selecting the type of the adhesive polymer binder as described above can adjust the adhesion between the coating and the adhesive polymer binder, can prevent the adhesive polymer binder from being dissolved by the electrolyte, and can minimize the resistance of the battery cell.

[0104] According to an embodiment of the present disclosure, the adhesive polymer binder may be disposed on a portion of the coating layer by spray coating, rod coating, spin coating, or dip coating. By selecting the method of disposing the adhesive polymer binder as described above, the adhesive polymer binder is easily disposed on the coating layer.

[0105] According to one embodiment of the present disclosure, the halogen atom may be a fluorine atom. As described above, the halogen atom is selected as a fluorine atom, and thus the wet adhesion of the separator may be improved, the rigidity of the pouch type battery cell may be improved, and the bending may be prevented.

[0106] According to one embodiment of the present disclosure, the metal atom may be one selected from the following: Al, Ba, Ti, Pb, Zr, La, Mg, Nb, Sr, Si, Y, Zn, Sn, Sb, Pt, and combinations thereof. Preferably, the metal atom may be Al (aluminum). The metal atom is selected from the above metal atoms, and thus the heat resistance of the separator may be ensured, the wet adhesion of the separator may be improved, the rigidity of the pouch-type battery cell may be improved, and bending may be prevented.

[0107] According to one embodiment of the present disclosure, the content of halogen atoms exposed from the surface of the coating 130 may be greater than 1 atom % or more, based on 100 atom % of the total atoms exposed from the surface of the coating 130. According to one embodiment of the present disclosure, the content of halogen atoms exposed from the surface of the coating 130 may be 1 atom % or more and 10 atom % or less, based on 100 atom % of the total atoms exposed from the surface of the coating 130. Specifically, the content of halogen atoms exposed from the surface of the coating 130 may be 2 atom % or more and 9 atom % or less, 3 atom % or more and 8 atom % or less, 4 atom % or more and 7 atom % or less, or 5 atom % or more and 6 atom % or less, based on 100 atom % of the total atoms exposed from the surface of the coating 130. The content of halogen atoms exposed from the surface of the coating 130 is adjusted within the above range, and thus the wet adhesion of the separator can be improved, the rigidity of the pouch-type battery cell can be improved, and bending can be prevented.

[0108] According to one embodiment of the present disclosure, the content of metal atoms exposed from the surface of the coating 130 may be 15 atomic % or more and 50 atomic % or less, based on 100 atomic % of the total atoms exposed from the surface of the coating 130. Specifically, the content of metal atoms exposed from the surface of the coating 130 may be 20 atomic % or more and 45 atomic % or less, 25 atomic % or more and 40 atomic % or less, or 30 atomic % or more and 35 atomic % or less, based on 100 atomic % of the total atoms exposed from the surface of the coating 130. The content of metal atoms exposed from the surface of the coating 130 is adjusted within the above range, and thus the heat resistance of the separator can be improved, the wet adhesion of the separator can be improved, the rigidity of the pouch-type battery cell can be improved, and bending can be prevented.

[0109] According to an embodiment of the present disclosure, the dry adhesive force of coating 130 can be 35gf / 20mm or larger. Specifically, the dry adhesive force of coating can be 35gf / 20mm or larger and 100gf / 20mm or smaller, 40gf / 20mm or larger and 95gf / 20mm or smaller, 45gf / 20mm or larger and 90gf / 20mm or smaller, 50gf / 20mm or larger and 85gf / 20mm or smaller, 55gf / 20mm or larger and 80gf / 20mm or smaller, 60gf / 20mm or larger and 75gf / 20mm or smaller or 65gf / 20mm or larger and 70gf / 20mm or smaller. As mentioned above, the dry adhesive force of coating is adjusted, and therefore the ease of assembly can be improved in the process of assembling electrode.

[0110] According to one embodiment of the present disclosure, the wet adhesion of the coating 130 may be 10gf / 20mm or more. Specifically, the wet adhesion of the coating may be 10gf / 20mm or more and 100gf / 20mm or less, 20gf / 20mm or more and 95gf / 20mm or less, 30gf / 20mm or more and 90gf / 20mm or less, 40gf / 20mm or more and 85gf / 20mm or less, 50gf / 20mm or more and 80gf / 20mm or less, 60gf / 20mm or more and 75gf / 20mm or less, or 65gf / 20mm or more and 70gf / 20mm or less. As described above, the wet adhesion of the coating is adjusted, and thus the rigidity of the pouch-type battery cell can be improved, and bending can be prevented.

[0111] In the present specification, the dry adhesion of the coating may mean the adhesion obtained by measuring the strength when the separator part of the sample is peeled off at an angle of 180° at a rate of 150 mm / min at 25°C, after the separator is cut into 70 mm (length) × 20 mm (width) and the prepared electrode and separator are laminated using a press at 60°C, 6.5 MPa and 1 second to make a sample, the prepared sample is attached and fixed to a glass plate using double-sided tape, and the sample is set so that the electrode faces the glass plate at this time.

[0112] In the present specification, the wet adhesion of the coating may mean the adhesion obtained by measuring the strength when the separator portion of the sample is peeled off at an angle of 90° at a rate of 200 mm / min at 25°C and fixed to a glass plate using a double-sided tape, after the separator is cut into 70 mm (length) × 20 mm (width) and the prepared electrode and separator are laminated using a press at 60°C, 6.5 MPa and 1 second to produce a sample, the prepared sample is loaded into a battery box together with an electrolyte (in which ethylene carbonate and ethyl methyl carbonate are mixed in a volume ratio of 7:3 and then prepared at a concentration of 1 MLiPF6), kept for 4 hours to impregnate the sample with the electrolyte, taken out of the box, and the prepared sample is attached and fixed to a glass plate using a double-sided tape, and the sample is set so that the electrode is facing the glass plate at this time.

[0113] One embodiment of the present disclosure provides a method for manufacturing a separator for an electrochemical device, the method comprising the following steps: mixing a slurry for a coating layer 130 comprising first polymer binder particles 131, second polymer binder particles 133, and inorganic particles 135 (S10); applying the slurry for coating layer to at least one surface of a porous polymer substrate 110 (S30); and providing a coating layer 130 by drying the slurry for coating layer (S50). Before drying to form a coating layer, the slurry may be kept wet to form at least two layers on the porous polymer substrate by gravity. After applying the slurry for coating layer to one surface of the porous polymer substrate 110 (S30), the slurry may be kept wet, for example, for at least 1 minute or longer, to phase separate by gravity of the coating layer. Phase separation by gravity may mean that the slurry may contain more than one phase and is separated due to different densities of the first polymer binder particles 131, the second polymer binder particles 133, and the inorganic particles 135 (S10). The inorganic particles 135 may be denser than the first polymer binder particles 131 and the second polymer binder particles 133, so that the inorganic particles 135 may form a bottom phase, and the first polymer binder particles 131 and the second polymer binder particles 133 may form a layer on the bottom phase. Therefore, phase separation does not mean that the phases need to form a clear separation phase, and it may be sufficient if a concentration gradient of the first polymer binder particles 131, the second polymer binder particles 133 or the inorganic particles 135 (S10) is formed between the upper phase and the lower phase.

[0114] The method for manufacturing a separator for an electrochemical device according to one embodiment of the present disclosure may maintain adhesion during lamination with an electrode, and may improve rigidity or prevent bending of a pouch-type battery cell by maintaining adhesion after battery activation.

[0115] According to one embodiment of the present disclosure, the method for manufacturing the separator 100 for an electrochemical device includes a step (S10) of mixing a slurry for coating containing first polymer binder particles 131, second polymer binder particles 133, and inorganic particles 135. As described above, the method includes a step (S10) of mixing a slurry for coating containing first polymer binder particles 131, second polymer binder particles 133, and inorganic particles 135, and thus a coating can be easily formed on the separator.

[0116] According to one embodiment of the present disclosure, the polymer binder resin (i.e., the first polymer binder particles 131 and the second polymer binder particles 133) can be dispersed in water as a suitable dispersion medium to prepare a polymer emulsion, thereby providing a slurry for a coating. By dispersing the first polymer binder particles 131 and the second polymer binder particles 133 in water as a suitable dispersion medium to prepare a polymer emulsion, thereby providing a slurry for a coating, pollutants generated during the manufacturing process can be minimized. In this specification, the dispersion medium is used in the process of preparing the slurry and may refer to a solvent.

[0117] According to one embodiment of the present disclosure, inorganic particles 135 may be added and dispersed in the polymer emulsion. The content ratio of the inorganic particles to the polymer binder particles is as described above and is appropriately adjusted in consideration of the thickness, pore size and porosity of the coating layer according to one embodiment of the present disclosure finally manufactured.

[0118] According to one embodiment of the present disclosure, a slurry for coating may be prepared by dispersing the first polymer binder particles 131 , the second polymer binder particles 133 , and the inorganic particles 135 in water as a dispersion medium.

[0119] According to one embodiment of the present disclosure, the solid content of the slurry for coating can be 10 wt % or more and 50 wt % or less. Specifically, the solid content of the slurry for coating can be 15 wt % or more and 40 wt % or less, 20 wt % or more and 35 wt % or less, or 15 wt % or more and 40 wt % or less. The solid content of the slurry for coating is adjusted within the above range, and thus the processability of the coating manufacturing process can be improved.

[0120] According to one embodiment of the present disclosure, the method for manufacturing a separator 100 for an electrochemical device includes a step (S30) of applying a slurry for coating to at least one surface of a porous polymer substrate 110. As described above, the step of applying the slurry for coating to at least one surface of the porous polymer substrate 110 is included, and thus the coating 130 can be formed with one application. Due to the separation between the inorganic particles and the polymer binder particles, the slurry for coating has an excess of inorganic particles 135 in a portion close to the porous polymer substrate 110, and has an excess of polymer binder particles 131 and 133 in a portion facing the porous polymer substrate 110 away from the porous polymer substrate 110, so that the adhesion to the electrode can be improved, and the porosity of the separator can be improved. In this specification, the presence of excess may mean that the content exceeds 50% by weight in the corresponding portion, and the portion close to the porous polymer substrate 110 and the portion away from the porous polymer substrate 110 can be divided based on an imaginary line at 1 / 2 thickness of the coating.

[0121] According to one embodiment of the present disclosure, the method of applying the slurry for coating to the surface of the porous polymer substrate 110 is not particularly limited to any one method, and a conventional method known in the art can be used. For example, various methods such as dip coating, die coating, roller coating, comma coating, or a combination thereof can be used.

[0122] According to one embodiment of the present disclosure, the method for manufacturing the separator 100 for an electrochemical device includes a step (S50) of providing the coating layer 130 by drying the slurry for coating. As described above, the step (S50) of providing the coating layer 130 by drying the slurry for coating is included, and thus damage to the coating layer can be minimized, and the dispersion medium contained in the slurry can be easily removed.

[0123] According to one embodiment of the present disclosure, the temperature of the drying process may be 25°C or higher and 75°C or lower. Specifically, the temperature of the drying process may be 30°C or higher and 70°C or lower, 35°C or higher and 65°C or lower, 40°C or higher and 60°C or lower, or 45°C or higher and 55°C or lower. Adjusting the temperature of the drying process within the above range can prevent the denaturation of the porous polymer substrate and can effectively remove the dispersion medium.

[0124] According to one embodiment of the present disclosure, during the drying process, time conditions are appropriately set to minimize the occurrence of surface defects of the coating 130. For drying, a drying auxiliary device such as a drying oven or hot air may be used within an appropriate range.

[0125] According to one embodiment of the present disclosure, the separator 100 is manufactured into an electrochemical device by a lamination process in which the separator 100 is between the negative electrode and the positive electrode and is bonded by applying heat and / or pressure. In one embodiment of the present disclosure, the lamination process can be performed by a rolling device including a pair of pressure rollers. That is, interlayer bonding can be achieved by sequentially stacking the negative electrode, the separator, and the positive electrode and placing them between the pressure rollers. At this time, the lamination process can be performed by a hot pressing method.

[0126] One embodiment of the present disclosure provides an electrochemical device 1000 including: a positive electrode 300 ; a negative electrode 500 ; and a separator 100 interposed between the positive electrode 300 and the negative electrode 500 .

[0127] The electrochemical device 1000 according to one embodiment of the present disclosure may reduce manufacturing costs and may facilitate manufacturing of the electrochemical device due to improved adhesion of the separator.

[0128] Figure 2FIG. 1 is a schematic diagram of an electrochemical device 1000 according to one embodiment of the present disclosure. Figure 2 , an electrochemical device according to an embodiment of the present disclosure will be described in detail.

[0129] In one embodiment of the present disclosure, an electrochemical device is a device that converts chemical energy into electrical energy by an electrochemical reaction, and is a concept covering primary batteries and secondary batteries. In this specification, a secondary battery can be charged and discharged, and means a lithium secondary battery, a nickel-cadmium battery, a nickel-hydrogen battery, etc. A lithium secondary battery is a battery using lithium ions as an ion conductor, and examples thereof may include a non-aqueous electrolyte secondary battery containing a liquid electrolyte, an all-solid-state battery containing a solid electrolyte, a lithium polymer battery containing a gel polymer electrolyte, a lithium metal battery in which lithium metal is used as a negative electrode, etc., but are not limited thereto.

[0130] According to one embodiment of the present disclosure, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on at least one surface of the current collector comprising a positive electrode active material, a conductive material and a binder resin. The positive electrode active material may include: a layered compound, such as a lithium manganese oxide composite material (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium manganese oxide, such as a compound of formula Li 1+ x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); represented by the formula LiMn 1-x M x A lithium manganese oxide composite material represented by LiMn2O4 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn); LiMn2O4, in which a portion of the Li in the formula is replaced by an alkaline earth metal ion; a disulfide compound; Fe2(MoO4)3; or a mixture of two or more thereof.

[0131] According to an embodiment of the present disclosure, the negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. The negative electrode may include, as the negative electrode active material, one selected from the following: lithium metal oxides; carbon, such as non-graphitizable carbon and graphite-based carbon; metal oxide composites, such as Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, and Group 3 elements of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers, such as polyacetylene; Li-Co-Ni-based materials; and titanium oxides; or a mixture of two or more thereof.

[0132] According to an embodiment of the present disclosure, the conductive material may be, for example, any one selected from the following: graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon, and polyphenylene derivatives, or a mixture of two or more conductive materials. More specifically, it may be one selected from the following: natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more conductive materials.

[0133] According to an embodiment of the present disclosure, the current collector is not particularly limited as long as it does not cause chemical changes in the relevant battery and has high conductivity. For example, stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. on its surface may be used.

[0134] According to an embodiment of the present disclosure, a polymer commonly used in electrodes in the art can be used as a binder resin. Non-limiting examples of such binder resins can include poly (vinylidene fluoride-co-hexafluoropropylene), polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer (polyethylene-co-vinyl acetate), polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, etc., but are not limited thereto.

[0135] According to one embodiment of the present disclosure, the positive electrode includes a positive electrode active material layer, and the coating layer of the separator is in direct contact with the positive electrode active material layer.

[0136] The coating of the present specification may have an improved thermal shrinkage. Thus, the minimized thermal shrinkage of the coating may help maintain the physical integrity of the separator-positive electrode interface during temperature changes caused by charge and discharge cycles. This in turn may result in improved electrochemical performance, such as better capacity retention and cycle stability. Thus, a stable separator-positive electrode interface may result in a longer life of the electrochemical device, which may be achieved due to reduced mechanical stress and enhanced cycle stability.

[0137] According to one embodiment of the present disclosure, the negative electrode includes a negative electrode active material layer, and the coating layer of the separator is in direct contact with the negative electrode active material layer.

[0138] The minimized thermal shrinkage of the coating can help maintain the physical integrity of the separator-anode interface during temperature changes caused by charge and discharge cycles. This in turn can result in improved electrochemical performance, such as better capacity retention and cycle stability. Therefore, a stable separator-anode interface can result in a longer life of the electrochemical device, which may be achieved due to reduced mechanical stress and enhanced cycle stability.

[0139] According to one embodiment of the present disclosure, the positive electrode slurry for preparing the positive electrode active material layer may include a dispersant, and the dispersant may be a pyrrolidone-based compound, specifically, N-methylpyrrolidone (ADC-01, LG Chem).

[0140] According to one embodiment of the present disclosure, based on 100 parts by weight of the positive electrode slurry, the dispersant may be included in the positive electrode slurry in an amount greater than 0 parts by weight and 0.5 parts by weight or less. Specifically, based on 100 parts by weight of the positive electrode slurry, the dispersant may be included in the positive electrode slurry in an amount greater than 0.05 parts by weight and 0.4 parts by weight or less.

[0141] According to one embodiment of the present disclosure, the negative electrode slurry for preparing the negative electrode active material layer may include a dispersant, and the dispersant may be a polypyrrolidone-based compound. Specifically, the dispersant may be polyvinyl pyrrolidone (Junsei, Japan).

[0142] According to one embodiment of the present disclosure, the dispersant may be included in the negative electrode slurry in an amount greater than 0 parts by weight and 0.5 parts by weight or less, based on 100 parts by weight of the negative electrode slurry. Specifically, the dispersant may be included in the negative electrode slurry in an amount greater than 0.05 parts by weight and 0.4 parts by weight or less, based on 100 parts by weight of the negative electrode slurry.

[0143] According to one embodiment of the present disclosure, a battery may be manufactured by loading the electrochemical device prepared as described above into an appropriate case and injecting an electrolyte.

[0144] According to one embodiment of the present disclosure, the electrolyte is + B - A salt of the structure + Including alkali metal cations such as Li + 、Na + and K + , or a combination thereof, and B - Including anions such as PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - and C(CF2SO2)3 - , or a combination thereof may include those dissolved or dissociated in an organic solvent consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone (γ-butyrolactone) or a mixture thereof, but is not limited thereto.

[0145] One embodiment of the present disclosure provides a battery module including a battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source, wherein the battery includes an electrochemical device. Specific examples of the device may include: an electric tool driven by an electric motor by receiving electric power; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc.; an electric two-wheeled vehicle, including an electric bicycle (E-bike) and an electric scooter (E-scooter); an electric golf cart; a power storage system; etc., but are not limited thereto.

[0146] Embodiments of the invention

[0147] Hereinafter, embodiments will be described in detail to explain the present disclosure in detail. However, embodiments according to the present disclosure may be modified in various forms, and the scope of the present disclosure is not to be construed as being limited to the embodiments described below. The embodiments of this specification are provided to more fully explain the present disclosure to those skilled in the art.

[0148] <Example 1>

[0149] A polyethylene resin (weight average molecular weight of 900,000) was extruded, and a porous polymer substrate (total thickness of about 9 μm, porosity of 40% by volume) was manufactured by a wet process.

[0150] The slurry for coating (solid content concentration of 20 wt %) was prepared by putting into water and dispersing styrene-butyl acrylate (glass transition temperature of 40° C.) as a first polymer binder particle with a particle size of 500 nm, a copolymer of PVdF and HFP with a substitution degree of 5 wt % (wherein HFP is included in the weight ratio of the polymer based on PVdF) as a binder based on polyvinylidene as a second polymer binder particle with a particle size of 500 nm, and inorganic particles (Al2O3, particle size of 500 nm). The weight ratio of the first polymer binder particle to the second polymer binder particle is 1:1, and the weight ratio of the polymer binder particle to the inorganic particle is 20:80. Based on the total weight of the coating composition, the obtained coating contains 6 wt % of fluorine atoms.

[0151] The slurry for coating was applied to both surfaces of the porous polymer substrate by a bar coating method using a doctor blade and dried with wind at 50° C. using a heat gun to form a coating layer with a thickness of 3 μm on each surface, so that a separator with a total thickness of 15 μm was manufactured.

[0152] Thereafter, the surface of the coating was measured by energy dispersive X-ray spectroscopy (EDS) (Hitachi, S-4800).

[0153] Figure 3 : is a photograph of the surface of Example 1 according to one embodiment of the present disclosure taken by energy dispersive X-ray spectroscopy (EDS) and a table showing the contents of elements provided on the surface. Figure 3 , on the surface of the coating of Example 1 above, the content of fluorine atoms was 4.26 wt %, and the content of aluminum atoms was 30.23 wt % (see Table 1).

[0154] <Comparative Example 1>

[0155] The separator was manufactured in the same manner as in Example 1, except that for Comparative Example 1, only styrene-butyl acrylate (glass transition temperature of 40° C.) which was an acrylic binder was used as the first polymer binder particles. The weight ratio of the polymer binder particles to the inorganic particles was 20:80. The obtained coating contained 0 wt % of fluorine atoms based on the total weight of the coating composition.

[0156] Figure 4 : is a photograph of the surface of Comparative Example 1 taken by EDS and a table showing the contents of elements provided on the surface. Figure 4 , on the surface of the coating layer of the above Comparative Example 1, the content of fluorine atoms was 0 wt %, and the content of aluminum atoms was 32.57 wt % (see Table 1).

[0157] <Comparative Example 2>

[0158] The separator was manufactured in the same manner as in Example 1, except that: for Comparative Example 2, only a copolymer of PVdF and HFP with a substitution degree of 5 wt % (wherein the weight ratio of HFP contained in the polymer based on PVdF) of a polyvinylidene-based binder was used as the second polymer binder particle. The weight ratio of the polymer binder particles to the inorganic particles was 20:80. Based on the total weight of the coating composition, the obtained coating contained 12 wt % of fluorine atoms.

[0159] Figure 5 : is a photograph of the surface of Comparative Example 2 taken by EDS and a table showing the contents of elements provided on the surface. Figure 5, on the surface of the coating layer of Comparative Example 2, the content of fluorine atoms was 13.92 wt %, and the content of aluminum atoms was 29.51 wt % (see Table 1).

[0160] <Comparative Example 3>

[0161] The separator is manufactured in the same manner as in Example 1 above, except that the slurry for the coating is prepared by putting and dissolving in acetone instead of water. It can be seen that the second polymer binder (i.e., a copolymer of PVdF and HFP) forms a network structure in which the particles are bonded and a gap of at least 10 μm is formed on the surface, which does not contain any particles. Therefore, the particles are not evenly distributed above the surface of the separator. Based on the total weight of the coating composition, the obtained coating contains 6% by weight of fluorine atoms.

[0162] Figure 6 : is a photograph of the surface of Comparative Example 3 taken by EDS and a table showing the contents of elements provided on the surface. Figure 6 , on the surface of the coating layer of the above Comparative Example 3, the content of fluorine atoms was 15.46 wt %, and the content of aluminum atoms was 31.51 wt % (see Table 1).

[0163] <Comparative Example 4>

[0164] A polyethylene resin (weight average molecular weight: 900,000) was extruded and a porous polymer substrate (total thickness: about 9 μm) was prepared by a wet process.

[0165] Preparation 50 Al2O3 powder with a particle size of 500nm was used as inorganic particles. Acrylic emulsion (CSB-130, Toyo Ink Co.) was prepared as the first polymer binder particles, and sodium carboxymethylcellulose (CMC-Na) (SG-L02, GL Chem Co.) was prepared as a dispersant. Based on the total weight of the coating composition, the obtained coating contained 0 wt% of fluorine atoms.

[0166] After the prepared inorganic particles, the first polymer binder particles, and the dispersant were added to water at a weight ratio of 97:2:1, the inorganic particles were pulverized and dispersed to prepare a slurry for coating.

[0167] Both surfaces of the porous polymer substrate are coated with the slurry for coating and dried to form a coating layer.

[0168] Figure 7 : is a photograph of the surface of Comparative Example 4 taken by EDS and a table showing the contents of elements provided on the surface. Figure 7, on the surface of the coating layer of Comparative Example 4, the content of fluorine atoms was 0 wt %, and the content of aluminum atoms was 36.96 wt % (see Table 1).

[0169] <Comparative Example 5>

[0170] A separator was manufactured in the same manner as in Example 1, except that no coating layer was formed unlike in Example 1 above.

[0171] Figure 8 : is a photograph of the surface of Comparative Example 5 taken by EDS and a table showing the contents of elements provided on the surface. Figure 8 , on the surface of the coating layer of Comparative Example 5, the content of fluorine atoms was 0 wt %, and the content of aluminum atoms was 0 wt % (see Table 1).

[0172] <Example 2>

[0173] In order to manufacture a separator, PVdF-HFP (the amount of HFP is 12 wt %, and the particle size is 300 nm) as an adhesive polymer binder is coated on the coating of the separator manufactured in Comparative Example 4 by a wire bar coating method so that the adhesive polymer binder is set to an area of ​​50% based on the total area of ​​the coating, and the separator is manufactured. Fig. 9 : is a photograph of the surface of Example 2 according to one embodiment of the present disclosure taken by EDS and a table showing the contents of elements provided on the surface. Fig. 9 , on the surface of the coating layer of Example 2 above, the content of fluorine atoms was 6.78 wt %, and the content of aluminum atoms was 28.00 wt % (see Table 1).

[0174] Table 1: Contents of elements measured by EDS

[0175]

[0176] Table 1 above shows the contents of elements measured by EDS of Examples 1 and 2 and Comparative Examples 1 to 5. The detected atoms are given in wt% (weight %) and atm% (atomic %) based on the total amount (ie, weight or atoms) of the elements measured on the surface by EDS.

[0177] <Manufacturing of Electrochemical Device>

[0178] 1) Manufacturing of positive electrode

[0179] The positive electrode active material (LiNi 0.8 Mn 0.1 Co 0.1O2), a conductive material (carbon black), a dispersant (N-methylpyrrolidone, ADC-01, LG Chem) and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a positive electrode active material layer having a concentration of 50 wt % of the remaining components except water. Next, the slurry was applied to the surface of an aluminum film (thickness of 10 μm) and dried to prepare a positive electrode with a positive electrode active material layer (thickness of 120 μm).

[0180] 2) Manufacturing of negative electrode

[0181] Graphite (a blend of natural graphite and artificial graphite), a conductive material (carbon black), a dispersant (polyvinyl pyrrolidone, Junsei, Japan) and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water at a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a negative electrode active material layer having a concentration of 50 wt % of the remaining components except water. Next, the slurry was applied to the surface of a copper thin film (thickness of 10 μm) and dried to prepare a negative electrode having a negative electrode active material layer (thickness of 120 μm).

[0182] <Experimental Example 1: Dry Adhesion Measurement>

[0183] The electrode and the separator prepared by cutting the separators of Example 1 and Comparative Examples 1 to 5 above into 70 mm (length) × 20 mm (width) were laminated to produce a sample using a press at 60°C, 6.5 MPa and 1 second. The prepared sample was attached and fixed to a glass plate using a double-sided tape, and at this time, the sample was set so that the electrode faced the glass plate. The separator portion of the sample was peeled off at an angle of 180° at a rate of 150 mm / min at 25°C, and the strength of each of the positive and negative electrodes at this time was measured and summarized in Table 1 below.

[0184] <Experimental Example 2: Wet Adhesion Measurement>

[0185] The electrode and the separator prepared by cutting the separators of the above Examples 1 and Comparative Examples 1 to 5 into 70 mm (length) × 20 mm (width) were laminated using a press at 60 ° C, 6.5 MPa and 1 second to produce a sample. The prepared sample was loaded into the battery box together with the electrolyte and kept for 4 hours, thereby impregnating the sample with the electrolyte. A mixture in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 7: 3 and then prepared at a concentration of 1M LiPF6 was used as the electrolyte. Thereafter, the sample was taken out of the box and attached and fixed to the glass plate using double-sided tape, and at this time, the sample was set so that the electrode faced the glass plate. The separator portion of the sample was peeled off at an angle of 90 ° at a rate of 200 mm / min at 25 ° C, and the strength of each of the positive and negative electrodes at this time was measured and summarized in Table 1 below.

[0186] <Experimental Example 3: Heat Shrinkage at 130°C>

[0187] The heat shrinkage was calculated by cutting the separators of Example 1 and Comparative Examples 1 to 5 above into a size of 50 mm (length) × 50 mm (width) to prepare a specimen, keeping it in an oven heated to 130° C. for 30 minutes, and then recovering the specimen and measuring its changed length for the machine direction (MD) and the transverse direction (TD):

[0188] Thermal shrinkage at 130°C (%) = {(size before shrinkage - size after shrinkage) / size before shrinkage} × 100

[0189] [Table 2]

[0190]

[0191] Referring to Table 2, it was confirmed that Examples 1 and 2 according to one embodiment of the present disclosure both had improved dry adhesion and wet adhesion and were excellent in terms of heat shrinkage.

[0192] In contrast, since the surface of the coating in Comparative Example 1 does not contain halogen elements, it is determined that the wet adhesion is rapidly reduced. Since the surface of the coating in Comparative Example 2 contains an excessive amount of halogen elements, it is determined that the manufacturing cost increases during the process of manufacturing the separator, and it is determined that the dry adhesion is reduced, and the wet adhesion to the negative electrode is rapidly reduced. Since acetone, which is an organic solvent, is used during the manufacturing process of the separator in Comparative Example 3, a separate device for solvent treatment is required, it is determined that the manufacturing cost increases. In Comparative Example 4, it is determined that the coating contains an excessive amount of inorganic material, and there is no adhesive layer, and therefore there is no adhesive force to the electrode. In Comparative Example 5, it is also determined that there is no coating and adhesive layer, and therefore there is no adhesive force to the electrode, and it is determined that thermal shrinkage occurs rapidly at high temperatures.

[0193] Therefore, the separator of the electrochemical device according to one embodiment of the present disclosure can improve both dry adhesion and wet adhesion and heat resistance by adjusting the weight of halogen atoms and metal atoms exposed by the coating layer.

[0194] [Explanation of Reference Numerals]

[0195] 100: Separator for electrochemical device 110: Porous polymer substrate

[0196] 130: Coating

[0197] 131: first polymer binder particles 133: second polymer binder particles 135: inorganic particles

[0198] 300: Positive

[0199] 500: Negative electrode 1000: Electrochemical device

Claims

1. A separator for an electrochemical device, comprising: a porous polymer substrate; as well as a coating disposed on at least one surface of the porous polymer substrate and comprising first polymeric binder particles, second polymeric binder particles, and inorganic particles, wherein the content of halogen atoms exposed from the surface of the coating layer is 10 wt % or less based on 100 wt % of total atoms exposed from the surface of the coating layer, the surface of the coating layer being the opposite surface to one surface on which the porous polymer substrate is provided; and The content of metal atoms exposed from the surface of the coating layer is 20 wt % or more based on 100 wt % of total atoms exposed from the surface of the coating layer.

2. The separator according to claim 1, wherein a ratio of a content of halogen atoms exposed from the surface of the coating measured in weight % based on 100 weight % of total atoms exposed from the surface of the coating to a content of halogen atoms in the coating measured in weight % based on 100 weight % of total atoms in the coating is in a range of 0.5 to 2.

5.

3. The separator according to claim 1, wherein a ratio of a content of metal atoms exposed from the surface of the coating measured in weight % based on 100 weight % of total atoms exposed from the surface of the coating to a content of halogen atoms exposed from the surface of the coating measured in weight % based on 100 weight % of total atoms exposed from the surface of the coating is in a range of 2.5 to 10. 4 . The separator according to claim 1 , wherein a content of halogen atoms exposed from the surface of the coating layer is 1 wt % or more and 10 wt % or less based on 100 wt % of total atoms exposed from the surface of the coating layer. 5 . The separator according to claim 1 , wherein a content of metal atoms exposed from the surface of the coating layer is 20 wt % or more and 50 wt % or less based on 100 wt % of total atoms exposed from the surface of the coating layer. The separator according to claim 1 , wherein the surface of the coating layer is uniformly distributed with pores.

7. The separator of claim 1, wherein a surface of the coating has a predominantly uniformly distributed particle-based morphology. 8 . The separator according to claim 1 , wherein the first polymer binder particles are acrylic binder particles. 9 . The separator according to claim 1 , wherein the second polymer binder particles are particles of a copolymer of polyvinylidene fluoride and hexafluoropropylene. 10 . The separator according to claim 1 , wherein the halogen atom is a fluorine atom.

11. The separator according to claim 1, wherein the metal atom is one selected from the group consisting of Al, Ba, Ti, Pb, Zr, La, Mg, Nb, Sr, Si, Y, Zn, Sn, Sb, Pt and combinations thereof, preferably Al, and / or The metal atoms are derived from the inorganic particles of the coating, wherein the inorganic particles are selected from BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT,0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), tin-zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5) and combinations thereof, preferably Al2O3. 12 . The separator according to claim 1 , wherein the dry adhesion of the coating layer may be 35 gf / 20 mm or more. 13 . The separator according to claim 1 , wherein the coating layer may have a wet adhesive force of 10 gf / 20 mm or more.

14. An electrochemical device comprising: a positive electrode; a negative electrode; and a separator according to any one of claims 1 to 13 interposed between the positive electrode and the negative electrode.

15. The electrochemical device according to claim 14, wherein the positive electrode comprises a positive electrode active material layer, and the coating layer of the separator is in direct contact with the positive electrode active material layer; and / or The negative electrode includes a negative electrode active material layer, and the coating layer of the separator is in direct contact with the negative electrode active material layer.

Citation Information

Patent Citations

  • A method for treating cancer or von Hippel-Lindau disease using a combination of an HIF-2 alpha inhibitor and lenvatinib.

    KR1020230026493A

  • Semiconductor package and method of manufacturing the same

    KR1020240007840A